2015
DOI: 10.1016/j.jtcvs.2014.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Reprint of: Reoperations on the total aortic arch in 119 patients: Short- and mid-term outcomes, focusing on composite adverse outcomes and survival analysis

Abstract: Aortic arch reoperations, although technically demanding, can produce acceptable results. Preoperative pulmonary disease, CPB time, and concomitant coronary artery bypass predicted an adverse outcome. The CPB time predicted mortality, and previous thoracoabdominal aortic surgery predicted stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
2
4
1
Order By: Relevance
“…It has been reported that 5-year survival after total arch replacement was 69.3% to 86.7% in 3.3 to 4.5 years of follow-up, and freedom from reoperation was 86.0% to 97.8% at 5 years. 12,[18][19][20][21][22] In comparison to our previous report (5-year survival was 79.6% AE 3.3% and 10-year survival was 71.2% AE 5.0% in 2.4 AE 2.3 years of follow-up, respectively), 7 our present study shows lower survival rates (73.1% AE 1.9% at 5 years and 54.8% AE 2.7% at 10 years). The difference in survival rates between our previous data and the current data can be attributed to our ability to analyze the number and the cause of late deaths more accurately (51 late deaths in our previous report and 190 late deaths in this report) in the longer follow-up period (5.0 AE 4.1 years and 97.1% patients were followed for longer than 1 year).…”
Section: Discussioncontrasting
confidence: 66%
“…It has been reported that 5-year survival after total arch replacement was 69.3% to 86.7% in 3.3 to 4.5 years of follow-up, and freedom from reoperation was 86.0% to 97.8% at 5 years. 12,[18][19][20][21][22] In comparison to our previous report (5-year survival was 79.6% AE 3.3% and 10-year survival was 71.2% AE 5.0% in 2.4 AE 2.3 years of follow-up, respectively), 7 our present study shows lower survival rates (73.1% AE 1.9% at 5 years and 54.8% AE 2.7% at 10 years). The difference in survival rates between our previous data and the current data can be attributed to our ability to analyze the number and the cause of late deaths more accurately (51 late deaths in our previous report and 190 late deaths in this report) in the longer follow-up period (5.0 AE 4.1 years and 97.1% patients were followed for longer than 1 year).…”
Section: Discussioncontrasting
confidence: 66%
“… 5 8 Reported rates of operative mortality range between 5 4 and 12%. 7 The observed rate of early mortality in this report was 6.7%, well comparable to other observations. 1 2 3 4 5 6 7 8 Several risk factors for early mortality have been reported, including previous Type A dissection, 5 older age, 3 and advanced NYHA class.…”
Section: Discussionsupporting
confidence: 91%
“… 7 The observed rate of early mortality in this report was 6.7%, well comparable to other observations. 1 2 3 4 5 6 7 8 Several risk factors for early mortality have been reported, including previous Type A dissection, 5 older age, 3 and advanced NYHA class. 3 6 Most of the publications reporting on RAAS found that indeed prolonged CPB time 3 6 7 8 independently predicts operative mortality.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations